Motivation and Technology Acceptance in a Neuroscience Student Lab—An Empirical Comparison Between Virtual Experiments With and Without Hands-on Elements - Formella-Zimmermann, Sandra; Kleespies, Matthias Winfried; Dierkes, Paul Wilhelm (Frontiers in Education, 2022)
Out-of-school laboratories, also called student labs, are an advantageous opportunity to teach biological subjects. Particularly in the case of complex fields such as neurobiology, student labs offer the opportunity to learn about difficult topics in a practical way. Due to numerous advantages, digital student labs are becoming increasingly popular nowadays. In this study, we investigated the effect of an electrophysiological setup for a virtual experiment with and without hands-on elements on participant motivation and technology acceptance. For this purpose, 235 students were questioned during a student laboratory day. The surveyed students showed high motivation and technology acceptance for the virtual experiment. In the comparison, the electrophysiological setup with hands-on elements performs better in the intrinsic components than the setup without hands-on elements: Thus, the hands-on approach is rated as more interesting and the perceived enjoyment scores higher. Nevertheless, both experimental groups show high values, so that the results of the study support the positive influence of digital laboratory as well as a positive influence of hands-on elements.